National Strategy for Youth Entrepreneurship Development in the Demographic Bonus - Rizkianoor, Muhammad Dwi (Riwayat: Educational Journal of History and Humanities, 2025)
Demographic bonus occurs when the proportion of the working-age population (1564 years) is greater than the non-working-age population (children under 14 years and seniors over 65 years). During this period, the dependency ratio decreases, per capita income has the potential to increase, and the economy grows faster. However, the demographic bonus phase will not last forever. After a transition period of approximately 50 years, the country will enter the post-demographic bonus phase, when the proportion of elderly people will increase significantly. Indonesia has been experiencing a demographic bonus since 2012, and it is expected to end around 2045, with a peak projected to occur around 2030. Youth, defined by the UN as individuals aged 1524, and according to Law Number 40 of 2009 concerning Youth, is defined as 1630 years old. Youth play a crucial role in this phase due to their creativity, innovation, and entrepreneurial potential. Unfortunately, the challenges facing youth entrepreneurship are growing in the demographic dividend. In the context of Indonesia's demographic dividend, youth entrepreneurship development strategies play a crucial role in harnessing the potential of its young population. The national strategy implemented to empower youth entrepreneurship, focusing on initiatives undertaken by the Indonesian government, highlights the importance of skills development, access to funding, and cultivating an entrepreneurial culture among youth. The analysis covers various programs aimed at increasing youth engagement in business activities, as well as the benefits of such strategies for economic growth and social development. By capitalizing on the demographic dividend, the country can transform its young workforce into a significant driver of innovation and economic prosperity.